Cognitive Effects of Astaxanthin Pretreatment on Recovery From Traumatic Brain Injury - Fleischmann, Chen; Shohami, Esther; Trembovler, Victoria; Heled, Yuval; Horowitz, Michal (Frontiers in Neurology, 2020)
Traumatic brain injury (TBI), caused by mechanical impact to the brain, is a leading cause of death and disability among young adults, with slow and often incomplete recovery. Preemptive treatment strategies may increase the injury resilience of high risk populations such as soldiers and athletes. In this work, the xanthophyll carotenoid Astaxanthin was examined as a potential nutritional preconditioning method in mice (sabra strain) to increase their resilience prior to TBI in a closed head injury (CHI) model. The effect of Astaxanthin pretreatment on HSP dynamics and functional outcome after CHI was explored by gavage or free eating (in pellet form) for two weeks before CHI. Assessment of neuro-motor function by the neurological severity score (NSS) revealed significant improvement in the Astaxanthin gavage treated group (100mg/Kg, ATX) during recovery compared to the gavage treated olive oil group (OIL), beginning at 24h post CHI, and lasting throughout 28d (p< 0.007). Astaxanthin pre-treatment in pellet form produced a smaller improvement in NSS vs. post-treatment at 7d post CHI (p<0.05). Cognitive and behavioral evaluation using the novel object recognition test (ORT), and the Y Maze test revealed an advantage for Astaxanthin administration via free eating vs. standard chow during recovery post CHI (ORT at 3 days, p<0.035; improvement in Y Maze score from 2 to 29 days, p<0.02). HSP profile and anxiety (open field test), were not significantly affected by Astaxanthin. In conclusion: Astaxanthin pre-treatment may contribute to improved recovery post TBI in mice and is influenced by the form of administration.